A Review Focused on Molecular Mechanisms of Anxiolytic Effect of Valerina officinalis L. in Connection with Its Phytochemistry through in vitro/in vivo Studies - Orhan, Ilkay E. (Current Pharmaceutical Design, 2021)
Valeriana officinalis L. (Valerianaceae) is one of the most reputed ancient medicinal plants used in modern phytotherapy and traditional medicine. Its root extract is one of the most effective herbal sedatives and tranquilizers, where the plant is also used for the treatment of gastrointestinal spasms. V. officinalis has complex phytochemistry consisting of the esterified iridoid derivatives known as valepotriates (e.g., valtrate, didrovaltrate, isovalerenic acid), sesquiterpenes (e.g., valerenic acid), flavonoids (e.g., linarin, apigenin), lignans (e.g., pinoresinol, hydroxypinoresinol), alkaloids (e.g., actinidine, valerine), triterpenes (e.g., ursolic acid), monoterpenes (e.g., borneol, bornyl acetate). Among them, valerenic acid is a marker compound for standardization of the root extracts of the plant and has been reported in many in vitro/in vivo studies to be responsible for anxiolytic action of the plant. Although modulation of gamma-aminobutyric acid (GABA) receptors has been revealed to be the leading mechanism of the plant-based on the existence of valerenic acid, several studies described the interaction of valerenic acid with glutamergic receptors. In addition to valerenic acid, isovaleric acid, didrovaltrate, borneol, and some lignans have also been proposed to contribute to the anxiolytic effect of the plant. In the current review, the data selectively scrutinized from the in vitro/in vivo studies about identifying anxiolytic molecular mechanisms of V. officinalis is focused.
Keywords: Valeriana officinalis